The application of multifactor model LITCAC in the organization of assembly work of flexible corrugated steel structures - Janusz, Leszek; Kapliński, Oleg (Technological and Economic Development of Economy, 2006)
Structural corrugated steel plate structures (SCSPS) are the subject of this paper. Some aspects of assembly of these structures are discussed, indicating factors of organization. The considerations are based on the estimation of labour consumption. On the grounds of regression and correlation one can create a new model of labour consumption and total costs of assembly work. This model is called LITCAC and constitutes “an open” type model. It is for estimating labour consumption, time and cost of assembly of CSPS in four modules. A combination of the new proposed model with the method of multi‐criteria optimization (in this case TOPSIS method) enables to improve the organization of predicting the job site progress as well as the cost related to site activities. Daugiafaktorio LITCAC modelio taikymas rifliuotųjų lakštinių metalinių konstrukcijų Santrauka. Nagrinėjami kai kurie rifliuotųjų lakštinių metalinių konstrukcijų montavimo organizavimo aspektai, įvertinant darbo sąnaudas. Taikant regresinę ir koreliacinę analizę, sukurtas modelis montavimo darbų sąnaudoms ir išlaidoms nustatyti. Šis modelis pavadintas LITCAC ir yra priskiriamas “atvirųjų” modelių klasei. Šis modelis sudarytas iš keturių modulių, skirtas metalinių konstrukcijų montavimo darbo sąnaudoms, trukmei ir kainai nustatyti. Pasiūlytojo modelio ir daugiakriterinės optimizacijos metodo (TOPSIS) integracija leidžia tiksliau suplanuoti darbus statybos aikštelėje bei nustatyti sąnaudas. Reikšminiai žodžiai: rifliuotosios lakštinės metalinės konstrukcijos, montavimo procesas, modeliavimas. First Published Online: 21 Oct 2010